Systematics Literature Review: The use of learning media to improve student's mathematical creative thinking skills in 21st century learning - Qoriaturrosyidah, Fitri; Simanjuntak, Friska Yanti; Mawaddah, Dina; Daniel Marpaung, Carlos Bettran; Hanggara, Yudhi; Ismarti, Ismarti; Hartanto, Suryo; Hermansah, Hermansah (Universitas Riau Kepulauan, 2025)
This research aims to review the literature related to the use of learning media in enhancing mathematical creative thinking skills. The method applied in this research is the Systematic Literature Review (SLR). As many as 20 articles were used as data sources in this study. Data were collected by reviewing all articles obtained from the period 2018 to 2023. To complete this research, various journal articles were collected through Google Scholar with the help of the Harzing's Publish or Perish application. The keywords in this article are